1995
DOI: 10.3382/ps.0740517
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Value of High-Oil Corn for Broiler Chicks

Abstract: A variety of corn (Natan) with high fat and protein contents (6.7 and 9.8%, respectively) was developed at Newe Ya'ar, Israel. The nutritive value of this corn for broiler chicks from 7 to 28 d of age was evaluated in two experiments. In the first experiment, Natan and a local conventional corn variety (LCC-2.9% fat and 7.2% protein) were incorporated in a relatively low-protein diet designated for the determination of AMEn by the substitution method. The AMEn content of Natan was found to be 3,658 kcal/kg, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…With HOC2 vs NC2 and HOC3 vs NC6, 100kcal/kg greater GE improved F/G by 0.05 units. Han et al (1987), Bartov and Bar-Zur (1995), Saleh et al (1997), andBenitez et al (1999) reported no significant difference in growth performance between broiler diets containing normal corn and HOC. This would be expected since their diets were formulated to be isonitrogenous and isocaloric, but same ratio of corn replacement could improve performance.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…With HOC2 vs NC2 and HOC3 vs NC6, 100kcal/kg greater GE improved F/G by 0.05 units. Han et al (1987), Bartov and Bar-Zur (1995), Saleh et al (1997), andBenitez et al (1999) reported no significant difference in growth performance between broiler diets containing normal corn and HOC. This would be expected since their diets were formulated to be isonitrogenous and isocaloric, but same ratio of corn replacement could improve performance.…”
Section: Resultsmentioning
confidence: 91%
“…Improving the nutritional value of corn through genetic alternation has become of great interest to poultry producers (Saleh et al, 1997). The published research regarding the utilization of high-oil corn (HOC) varieties (Han et al, 1987;Dale and Whittle, 1991;Adams et al, 1994;Bartov and Bar-Zur, 1995;Saleh et al, 1997;Parsons et al, 1998;Benitez et al, 1999;Lee et al, 2001) typically has been limited in scope, due in part to limitation of test material available. Also due to the development of new varieties of HOC yearly, recent studies are limited and somewhat conflicting in their results.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that HOM can be used to increase the energy density of diets without the use of high concentrations of supplemental fat (Adams et al, 1994). It should be noted that, in spite of the high nutritional value of HOM, there was only a slight improvement in chicken performance when the HOM replaced NM in a well-balanced diet (Bartov and Bar-Zur, 1995). For LPM, a study with pigs has shown that a higher daily nitrogen retention was observed among pigs that received diets containing LPM than those fed on diet containing NM (Sands et al, 2001) suggesting a possible interaction between nitrogen and phosphorus balance in pigs.…”
Section: Value Of Ingredients For Ducksmentioning
confidence: 88%
“…Smink et al (2008) concluded that randomized palm oil may be used as vegetable oil in broiler nutrition with positive effect on saturated fatty acid digestibility when compared with native palm oil and positive effect on firmness of meat when compared with vegetable oils rich in unsaturated fatty acids. Bartov and Bar-Zur, (1995) broilers from 8 to 21 days consuming diets with HOC developed showed no differences in feed intake or weight gain, but feed efficiency was better when compared with a conventional corn. Han et al (1987) reported that weight gain, gain-to-feed ratio, and skin and plasma pigmentation were improved in chicks fed HOC compared to those fed conventional yellow dent corn.…”
Section: Introductionmentioning
confidence: 90%